ASSESING CRITICAL LENGTH OF DRY SPEEL FOR CROP GROWTH BASED ON SOIL WATER BALANCE AT PENGALENGANPENGKAJIAN DERET HARI KERING KRITIS BERDASARKAN NERACA AIR DI PENGALENGAN - Rizaldi Boer; Mugni Hadi Hariadi (Agromet, 2004)
Abstract is available in the full text (pdf format)